Qualitative Inquiry and the Politics of Advocacy. - Denzin, Norman K. (International Congress of Qualitative Inquiry, 2012)
The plenary volume from the Seventh International Congress of Qualitative Inquiry (2011) examines the politics of advocacy and the context in which scholars are encouraged to pursue social justice agendas, be human rights advocates, and do work that honors the core values of human dignity and freedom from fear and violence. Contributions from many of the world's leading qualitative researchers in communications, education, sociology, and related disciplines address topics including community research, transformative education, and researcher ethics, and guide the field toward an engaged, activ.